A cellular memory mechanism aids overload hypertrophy in muscle long after an episodic exposure to anabolic steroids. (22nd November 2013) - Egner, Ingrid M.; Bruusgaard, Jo C.; Eftestøl, Einar; Gundersen, Kristian
Key points: Training studio folklore suggests that previous strength training, with or without the use of anabolic steroids facilitates re‐acquisition of muscle mass even after long intervening periods of inactivity. This 'muscle memory' has previously been attributed to motor learning, but our data suggest the existence of a cellular memory residing in the muscle fibres themselves. Muscle fibres have multiple nuclei, and the number of nuclei increases when muscle mass increases. When mice were briefly treated with steroids the muscle mass and number of nuclei increased. The drug was subsequently withdrawn for 3 months and the muscle mass returned to normal, but the excess cell nuclei persisted. When such muscles were subjected to overload they grew by 30% over 6 days while controls grew insignificantly. Our data suggest that previous strength training might be beneficial later in life, and that a brief exposure to anabolic steroids might have long lasting performance‐enhancing effects. Abstract Previous strength training with or without the use of anabolic steroids facilitates subsequent re‐acquisition of muscle mass even after long intervening periods of inactivity. Based on in vivo and ex vivo microscopy we here propose a cellular memory mechanism residing in the muscle cells. Female mice were treated with testosterone propionate for 14 days, inducing a 66% increase in the number of myonuclei and a 77% increase in fibre cross‐sectional area. Three weeks after removing the drug, fibre size was decreased to the same level as in sham treated animals, but the number of nuclei remained elevated for at least 3 months (>10% of the mouse lifespan). At this time, when the myonuclei‐rich muscles were exposed to overload‐exercise for 6 days, the fibre cross‐sectional area increased by 31% while control muscles did not grow significantly. We suggest that the lasting, elevated number of myonuclei constitutes a cellular memory facilitating subsequent muscle overload hypertrophy. Our findings might have consequences for the exclusion time of doping offenders. Since the ability to generate new myonuclei is impaired in the elderly our data also invites speculation that it might be beneficial to perform strength training when young in order to benefit in senescence.